2021
DOI: 10.3389/fonc.2021.654472
|View full text |Cite
|
Sign up to set email alerts
|

The lncRNA ADAMTS9-AS2 Regulates RPL22 to Modulate TNBC Progression via Controlling the TGF-β Signaling Pathway

Abstract: BackgroundLong non-coding RNAs (lncRNAs) are key regulators of triple-negative breast cancer (TNBC) progression, but further work is needed to fully understand the functional relevance of these non-coding RNAs in this cancer type. Herein, we explored the functional role of the lncRNA ADAMTS9-AS2 in TNBC.MethodsNext-generation sequencing was conducted to compare the expression of different lncRNAs in TNBC tumor and paracancerous tissues, after which ADAMTS9-AS2differential expression in these tumor tissues was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…Several bioinformatic studies found that high expression of Z68871.1 and SPRY4-AS1 were correlated with worse OS in solid tumors including BC, HCC, and squamous cell carcinoma [69][70][71][72][73]. High expression of ADAMTS9-AS2 was related to a better treatment response and prognosis in BC [74,75], which was coherent with our results. However, high expression of COL4A2-AS1, CCDC144NL-AS1, and ADAMTS9-AS2 were related to proliferation and worse prognosis of breast, gastric, colorectal cancer, HCC, and lung cancer [76][77][78][79][80][81].…”
Section: Discussionsupporting
confidence: 90%
“…Several bioinformatic studies found that high expression of Z68871.1 and SPRY4-AS1 were correlated with worse OS in solid tumors including BC, HCC, and squamous cell carcinoma [69][70][71][72][73]. High expression of ADAMTS9-AS2 was related to a better treatment response and prognosis in BC [74,75], which was coherent with our results. However, high expression of COL4A2-AS1, CCDC144NL-AS1, and ADAMTS9-AS2 were related to proliferation and worse prognosis of breast, gastric, colorectal cancer, HCC, and lung cancer [76][77][78][79][80][81].…”
Section: Discussionsupporting
confidence: 90%
“…ADAMTS9‐AS2 controls cancer cell behavior by modulating TGF‐β signaling in breast cancer and tongue squamous cell carcinoma. 41 , 42 Interestingly, TGFβ is reported to promote cell migration and metastasis by inducing epithelial‐mesenchymal transition (EMT), while inhibiting cell proliferation by inducing G1 phase cell cycle arrest in human oral cancer cells. 43 In addition, ADAMTS9‐AS2 regulates FOXO1 in clear cell RCC.…”
Section: Discussionmentioning
confidence: 99%
“…Additional lncRNAs reported as potentially poor prognostic markers for TNBC patients were the tumor suppressor candidate 7 ( TUSC7 ) and ADAMTS9 antisense RNA 2 ( ADAMTS9-AS2 ) ( 17 , 18 ). TUSC7 can bind to miR-1224-3p , and its overexpression decreased cell motility and promoted the sensitivity of MDA-MB-468 cells to cytotoxic drugs, while TUSC7 knockdown in MDA-MB-231 cells enhanced TGFBR2 levels, suggesting a negative role of TUSC7 on TGF-β signaling ( 18 ).…”
Section: Breast Cancermentioning
confidence: 99%
“…TUSC7 can bind to miR-1224-3p , and its overexpression decreased cell motility and promoted the sensitivity of MDA-MB-468 cells to cytotoxic drugs, while TUSC7 knockdown in MDA-MB-231 cells enhanced TGFBR2 levels, suggesting a negative role of TUSC7 on TGF-β signaling ( 18 ). Furthermore, ADAMTS9-AS2 can interact with and modulate the expression of the ribosomal protein L22 (RPL22) ( 17 ). These data were further correlated with the translational downregulation of TGFBRI and SMAD2 , thereby modulating TGF-β signaling negatively.…”
Section: Breast Cancermentioning
confidence: 99%